SATU ABAD PERUBAHAN SAKRALITAS ALAM MALIND-ANIM - Muntaza Muntaza (Jurnal Sosiologi Reflektif, 2013)
“This paper aims to show how sacred over nature (including land)that is attached over century by Malind-Anim changed by power ofmoney. This sacred over nature closely related to how realm of thoughtof Malind-Anim over their space of life. The Changes of sacred natureof Malind-Anim should be traced in long duration. This paper wouldexamined those changes since the Dutch Colonial era until present,with the presence of MIFEE”